Queue System Analysis for Civil Servants' Rice Distribution Based on Web Platform at the Wamena Post Office, Papua Pegunungan - Tabuni, Yohanes (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to create and evaluate a queue system for the distribution of rice quotas to civil servants (PNS) at the Wamena Post Office in the mountainous province of Papua. The study will utilize a User-Centered Design approach, encompassing phases such as user needs analysis, prototype design, website development, and user testing and evaluation. The results of the implementation and testing of the civil servants' rice quota queue system application at the Wamena Post Office indicate that the development of the application can be successful through the integration of both web and Android application platforms. Through this integration, the queue system has successfully transformed into a directly integrated and real-time online queue system. It aims to enhance the efficiency and effectiveness of public services for civil servants and the community when obtaining goods and services at the post office.